Does Performance Management Relate to Good Governance? A Study of Its Relationship with Citizens' Satisfaction with and Trust in Israeli Local Government. Issue 2 (4th March 2019) - Beeri, Itai; Uster, Anna; Vigoda-Gadot, Eran
ABSTRACT: Since the late 1980s, performance management has become a bon ton in central and local government research and practice. Its emergence is largely a result of neo-liberal ideas and the reforms of New Public Management. The goal of this study is to examine the relationship between performance management at the local level and citizens' satisfaction with and trust in government. By using data collected by Israeli local authorities over recent years, several questions were answered. Have years of performance management initiatives been effective in terms of good governance? What relationship do they have with citizens as service recipients? What are the implications of this experience for future reforms in public administration? Three data sets were used concerning (1) citizens' satisfaction with and trust in government, (2) the experiences of senior local government officers with performance management initiatives, and (3) the objective characteristics of the local government authorities. Results indicate that performance management is associated with higher levels of citizens' trust in and satisfaction with local government. Furthermore, the community's socioeconomic status moderates the mediated relationship between performance management and the satisfaction and trust of citizens. Implications of these findings are discussed, and suggestions for future studies are recommended.